2014
DOI: 10.1590/s2317-17822014000100004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of risk groups for oropharyngeal dysphagia in hospitalized patients in a university hospital

Abstract: Purpose: To identify risk groups for oropharyngeal dysphagia in hospitalized patients in a university hospital. Methods: The study was design as an exploratory cross-sectional with quantitative data analysis. The researched population consisted of 32 patients admitted to the medical clinic at the university hospital. Patient history data were collected, followed by a universal swallowing screening which included functional feeding assessment, to observe clinical signs and symptoms of dysphagia, and assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
15

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 40 publications
0
34
0
15
Order By: Relevance
“…In this study, /m/, /t/, and /g/ were used as the speech stimuli in different frequencies and it was found that the impact of these speech stimuli did not differ significantly in generating the P1 latency. A few studies showed that different stimulus types, such as pure tone, click, a speech stimulus used in generating P1 did not change the P1 latency [18,[22][23][24][25]. In this study, the P1 latency values were combined so that it was possible to analyse more data at the same time.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, /m/, /t/, and /g/ were used as the speech stimuli in different frequencies and it was found that the impact of these speech stimuli did not differ significantly in generating the P1 latency. A few studies showed that different stimulus types, such as pure tone, click, a speech stimulus used in generating P1 did not change the P1 latency [18,[22][23][24][25]. In this study, the P1 latency values were combined so that it was possible to analyse more data at the same time.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have found that while the P1 component can be recorded in all children, the P2 response can only be reliably detected at $ 2 years old. Additionally, chronological age has been found to be the most influential variable in the devel-opment of auditory pathways, since the latency of CAEP components appear to decrease in direct proportion to the age of the subject 4,5,7,8,27 . As shown in ►Table 1, all 19 participants in the present study displayed the P1/N1 components, while 17 displayed the P2/N2 component at 2 years old.…”
Section: Discussionmentioning
confidence: 99%
“…3 In neonates and infants, the study of AEPs contributes to the assessment of the sensitivity, maturation, and neuroplasticity of auditory pathways, consisting an important source of information on auditory processing and the potential need of sound amplification, facilitating the implementation of early intervention programs, if necessary. [4][5][6][7][8] Cortical auditory evoked potentials (CAEPs) are longlatency responses also known as exogenous potentials, since they are determined by the physical properties of the stimulus rather than by the response of the subject. Cortical…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respiratory diseases, chronic obstructive pulmonary disease, and xerostomia, were indicated as risk factors for oropharyngeal dysphagia [3]. Another retrospective study reported a high incidence of risk for oropharyngeal dysphagia in hospitalized patients, and hospitalized patients with CHF.…”
Section: Introductionmentioning
confidence: 99%